Liposome Formulation of Fullerene-Based Molecular Diagnostic and Therapeutic Agents - Zhiguo Zhou (MDPI AG, 2013)
Fullerene medicine is a new but rapidly growing research subject. Fullerene has a number of desired structural, physical and chemical properties to be adapted for biological use including antioxidants, anti-aging, anti-inflammation, photodynamic therapy, drug delivery, and magnetic resonance imaging contrast agents. Chemical functionalization of fullerenes has led to several interesting compounds with very promising preclinical efficacy, pharmacokinetic and safety data. However, there is no clinical evaluation or human use except in fullerene-based cosmetic products for human skincare. This article summarizes recent advances in liposome formulation of fullerenes for the use in therapeutics and molecular imaging.